2019
DOI: 10.1371/journal.pone.0216833
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathy-related mutations alter the membrane binding properties of the human myelin protein P0 cytoplasmic tail

Abstract: Schwann cells myelinate selected axons in the peripheral nervous system (PNS) and contribute to fast saltatory conduction via the formation of compact myelin, in which water is excluded from between tightly adhered lipid bilayers. Peripheral neuropathies, such as Charcot-Marie-Tooth disease (CMT) and Dejerine-Sottas syndrome (DSS), are incurable demyelinating conditions that result in pain, decrease in muscle mass, and functional impairment. Many Schwann cell proteins, which are directly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 63 publications
3
34
0
Order By: Relevance
“…The narrow extracellular space between pairs of compact myelin membranes, the intramyelinic compartment, is compacted by a densely arranged P0 zipper in the PNS, which dictates the stability and width of this compartment [28,[37][38][39][40][41]. While numerous studies have specifically focused on the compaction of the intramyelinic compartment, P0 has also been shown to stabilize membrane stacking in the narrow cytoplasmic compartment [42,43]; this is supported by recent biophysical experiments using model membranes [41,44]. In animal models, the stacking occurs in the absence of cytosolic MBP and P2 [42,45,46], which poses open, neglected questions, as cytoplasmic membrane leaflet adhesion by P0 remains poorly understood.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…The narrow extracellular space between pairs of compact myelin membranes, the intramyelinic compartment, is compacted by a densely arranged P0 zipper in the PNS, which dictates the stability and width of this compartment [28,[37][38][39][40][41]. While numerous studies have specifically focused on the compaction of the intramyelinic compartment, P0 has also been shown to stabilize membrane stacking in the narrow cytoplasmic compartment [42,43]; this is supported by recent biophysical experiments using model membranes [41,44]. In animal models, the stacking occurs in the absence of cytosolic MBP and P2 [42,45,46], which poses open, neglected questions, as cytoplasmic membrane leaflet adhesion by P0 remains poorly understood.…”
Section: Introductionmentioning
confidence: 83%
“…Cells 2020, 9, 1832 3 of 20 biophysical characterizations using simplified lipid compositions have been performed on P0ct, which revealed that P0ct alone is an IDP in solution but folds upon irreversible association with negatively charged detergent micelles and lipid vesicles [58][59][60][61]. P0ct embeds deep into the lipid structure and affects the mechanical and thermodynamic properties of its surroundings [41,44]. This association in simplified model systems is influenced by ionic strength and the presence of Ca 2+ [62], and it generally resembles the behavior of MBP under similar conditions, which involves a large gain of structural content [41,[58][59][60][61]63].…”
Section: The Molecular Structure Of P0mentioning
confidence: 99%
See 2 more Smart Citations
“…However, these structures are very close to the myelin membrane and therefore likely to be folded, as experimentally shown for the loops of proteolipid protein [23]. Another example is the C-terminal extension of P0 (P0ct), which is disordered in the absence of lipids, but not under membrane-like conditions [19,[51][52][53][54]. In vivo, the lipidated P0ct directly follows the transmembrane helix of P0 in the cytoplasmic compartment of PNS compact myelin, permanently anchoring it to the phospholipid membrane, whereby it folds and is thus unlikely to function as a canonical IDP [55].…”
Section: General Attributes Of Myelin-specific Proteinsmentioning
confidence: 85%